Intravital microscopy to study myocardial engraftment - Lushaj, Entela B. (Oxford University Press, 2012)
Tissue engineering and stem cell transplantation are promising novel therapies for myocardial repair. A major barrier to cell survival after transplantation involves inadequate vascularization. Continuous observation of cardiac tissue engraftment and angiogenesis could help understand these processes and allow for identification of the optimal conditions for these therapeutic interventions. We investigated the ability of a skin-fold chamber model to allow for engraftment of differentiated myocardial tissue in mice. Neonatal atrial and ventricular tissues were implanted in the in vivo chambers. All myocardial implants had a high rate of engraftment (86–95%). Tissue engraftment was preceded by a ‘bleeding phase’ in both the atrial and ventricular implants. This occurred earlier in ventricular compared with atrial implants. Spontaneous contractions were observed after an average of 13 days after implantation in all chambers but occurred earlier in ventricular compared with atrial implants. The host cells surrounded the myocardial implants circumferentially, but have limited infiltration into these grafts. This is the first report of successful ectopic engraftment of differentiated myocardium using a skin-fold chamber. This model is invaluable for real-time observation of early angiogenesis and tissue growth during in vivo myocardial engineering and myocardial regeneration.